Intra- and extra-oral halitosis: finding of a new form of extra-oral blood-borne halitosis caused by dimethyl sulphide - Albert Tangerman (Blackwell Synergy, 2007)
Aim: The aim of this study was to unravel the origen and cause of intra-oral and extra-oral halitosis. Material and Methods: We studied 58 patients complaining of halitosis, using gas chromatography of volatile sulphur compounds (VSCs) in mouth and nose breath, organoleptic scoring of mouth and nose breath, Halimeters readings of mouth air and tongue-coating inspection. Subjects had no precence or history of periodontitis. Result: Of 58 patients, 47 patients had halitosis of oral origin, six had halitosis of extra-oral origin and five had no halitosis (halitophobia). A strong correlation was found between the degree of intra-oral halitosis as measured by organoleptic scoring of mouth breath and the concentration of the VSCs hydrogen sulphide (H2S) and methyl mercaptan (CH3SH) in mouth breath. Taking into account the much larger odour index of CH3SH, it was concluded that CH3SH is the main contributor to intra-oral halitosis. In all six cases of extra-oral halitosis, halitosis was caused by the presence of elevated levels of dimethyl sulphide (CH3SCH3) in mouth and nose breath. Conclusion: Our study provides evidence that the VSC, CH3SH and to a lesser extent H2S are the main contributors to intra-oral halitosis and that CH3SCH3 is the main contributor to extra-oral or blood-borne halitosis, due to a hitherto unknown metabolic disorder.